Identification of fast ion wall loads in Wendelstein 7-X from thermographic measurements. (1st December 2022) - Cornelissen, Mark J H; Lazerson, Samuel A; Gao, Yu; Proll, Josefine H E; McNeely, Paul; Rust, Norbert; Hartmann, Dirk; Jakubowski, Marcin W; Ali, Adnan; Pisano, Fabio; Niemann, Holger; Puig Sitjes, Aleix; et al.
Abstract: Fast ion wall loads can result in excessively high heat fluxes to the plasma-facing components (PFCs). To allow for the development of mitigation strategies, and thereby protect the PFCs, the fast ion losses have to be predicted by faithful models. To ensure that fast ion models are an accurate representation of the real world, they need to be verified. The neutral-beam experiments performed in Wendelstein 7-X (W7-X) allow to investigate and verify models of the fast ion losses in the stellarator configuration. Infrared thermographic measurements were used to obtain the heat flux to both the baffle plates and the divertor. We found evidence of fast ion wall loads on the baffle plates, with loads between 100 kW m −2 and 1 MW m −2 . The loads are attributed to fast ions which escape the main plasma via magnetic ripples. The fast ion wall loads on the baffle plates show up-down and toroidal asymmetry. The experimental results were compared to numerical simulations performed by the BEAMS3D and ASCOT codes. Qualitative agreement in up-down asymmetry is found, but the magnitude and toroidal asymmetry are not yet well predicted by the simulations. The asymmetries of the strike lines on the divertor suggest that fast ions also play a role here. Specifically, a second strike line emerged consistently in the high-iota configuration on the horizontal divertor. The shape and magnitude of the strike lines changed considerably during the neutral-beam injection (NBI) operation phase. Although no damage to steel components of W7-X was found, fast ion loads to the baffle plates could possibly limit the NBI operation in the upcoming campaigns of W7-X.